Health Literacy and Health Care System Confidence as Determinants of Attitudes to Vaccines in France: Representative Cross-Sectional Study - Georges Khoury; Jeremy K Ward; Julien Mancini; Amandine Gagneux-Brunon; Liem Binh Luong Nguyen (JMIR Publications, 2024)
BackgroundHealth literacy involves individuals' knowledge, personal skills, and confidence to take action to evaluate and appraise health-related information and improve their health or that of their community. ObjectiveThis study aimed to analyze the association between health literacy and attitude toward vaccines, adjusted with other factors. MethodsWe used the SLAVACO Wave 3, a survey conducted in December 2021 among a sample of 2022 individuals, representative of the French adult population. We investigated factors associated with the attitude toward vaccines using respondents' different sociodemographic data, health literacy levels, and the health care system confidence levels using a multinomial logistic regression analysis. ResultsAmong the participants, 440.4 (21.8%) were classified as "distrustful of vaccines in general," 729.2 (36.1%) were "selectively hesitant," and 852.4 (42.2%) were "nonhesitant." In our model, the level of health literacy was not statistically different between the "distrustful of vaccines in general" and the "selectively hesitant" (P=.48), but it was associated with being a "nonhesitant" (adjusted odds ratio [aOR] 1.86, 95% CI 1.25-2.76). The confidence in the health care system was a strong predictor for a "nonhesitant" attitude toward vaccines (aOR 12.4, 95% CI 7.97-19.2). We found a positive correlation of 0.34 (P<.001) between health literacy and confidence in the health care system, but the interaction term between health literacy and health care system confidence was not significant in our model. ConclusionsHealth literacy was associated with a "nonhesitant" attitude toward vaccines. The findings demonstrated that health literacy and confidence in the health care system are modestly correlated. Therefore, to tackle the subject of vaccine hesitancy, the main focus should be on increasing the population's confidence and on increasing their health literacy levels or providing vaccine information addressing the needs of less literate citizens.